2014
DOI: 10.2319/072914-530.1
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of TMJ disorders in adults after adolescent Herbst therapy: A 6-year and 32-year radiographic and clinical follow-up study

Abstract: Objective: To analyze radiographic signs of temperomandibular joint (TMJ) osteoarthritis and clinical TMJ symptoms in patients 6 years and 32 years after treatment with a Herbst appliance. Materials and Methods: Fourteen patients were derived from a sample of 22 with Class II division 1 malocclusions consecutively treated with a banded Herbst appliance at the age of 12-14 years old (T1-T2). The subjects were reexamined after therapy at the ages of 20 years (T3) and 46 years (T4). The TMJs of the 14 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
11
0
3
Order By: Relevance
“…The 13 articles in this review were published between 2014 and 2020. Ten were prospective [24][25][26][27][28][29][30][31][32][33] and 3 were retrospective studies. [34][35][36] Five of the prospective studies were controlled, [26][27][28]30,32 and 5 were not controlled.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 articles in this review were published between 2014 and 2020. Ten were prospective [24][25][26][27][28][29][30][31][32][33] and 3 were retrospective studies. [34][35][36] Five of the prospective studies were controlled, [26][27][28]30,32 and 5 were not controlled.…”
Section: Resultsmentioning
confidence: 99%
“…16 In this context, previous investigations have indicated that conducting orthodontic treatment did not significantly impact the risk of developing temporomandibular joint disorders in patients suffering from class II and III skeletal malocclusions, whether by decreasing or increasing the estimated risk. [17][18][19] Besides, in cases of retracted maxillary teeth, it has been demonstrated that conducting premolar extractions modality was associated with manifestations of a posterior repositioning of the condyles as assessed using cone-beam computed tomography imaging modalities. 20 However, evidence regarding the impact of the approach on the induction of disc displacement is still poorly reported, and further investigations are required to comprehend this association furtherly.…”
Section: Discussionmentioning
confidence: 99%
“…Sonuç olarak, Herbst tedavisinin uzun süreli takip çalışmasında, hastaların TME bulgularının genel popülasyondaki bireylerle benzer olduğu, TME'de sadece küçük komplikasyonların tespit edildiği ve bu nedenle uzun dönemde Herbst apareyinin TME için zararlı olmadığı iddia edilmiştir. 55 6. Relaps Relaps genel olarak ortodontik anomalilerin tedavisinden sonra kaçınılmaz olarak, değişen oranlarda olmak üzere tüm vakalarda bildirilmektedir.…”
Section: Temporomandibular Eklemle Ilgili Komplikasyonlarunclassified